Guide to information technology; cyber laws and E-commerce / by Shakil Ahmad Syed and Rajiv Raheja - Syed, Shakil Ahmed (Delhi, 2001)
India's future roadmap will be dominated by the plans of e-governance. Knowledge is nobody's monopoly and now through the media of Internet, an invention of a new idea or discovery at a distant corner of the globe can be made available at the finger-tips of persons all over the world. It is now several months since the infotech industry virtually swept our country and the country is getting more work done in less time. E-governance has been broadly stated as the application of information technology to the process of government functionary to bring about simple, moral, accountable, responsible and transparent governance. E-governance completely changed the profile of citizens and the ways of conducting business. How quickly the new boom has been changing the conventional facets of the world so drastically-politically, intellectually, socio- economically, educationally and so on? Capital's A GUIDE TO INFORMATION TECHNOLOGY succinctly and comprehensively tries to delve into this question with special emphasise on the application of Infotech in Indian scenario in a concise manner.
Keywords: Computer Network- law and legislation